Branding Nationalism: Identity Conflicts and Cultural Representation in Local Product Advertising - Afifatur Rohimah; Ries Dyah Fitrianti (AIBPM Publisher, 2025)
This study critically explores how nationalism is branded and commodified through local product advertising in Indonesia. Grounded in theories of cultural branding and identity politics, it investigates how advertising constructs, negotiates, and commercializes national identity within a globalized market context. Using qualitative content analysis of selected local brand campaigns, the research reveals that nationalism in advertising operates as both empowerment and control: it promotes collective pride while reinforcing social hierarchies and selective cultural inclusion. Local brands frequently employ traditional symbols, language, and imagery to evoke authenticity, yet these representations often serve commercial rather than cultural purposes. Consequently, local advertising becomes a contested site where culture is simultaneously celebrated and commodified. The study argues that such branding practices transform nationalism into a consumable aesthetic, blurring the line between civic identity and consumer desire. These findings underscore the need for critical media literacy and reflexive communication practices in interpreting the socio political implications of cultural representation in advertising.